Unraveling the Threads of Time: An Analysis of Literature on Strategies for Teaching Simple Past Tense in Higher Education - Mike Nurmalia Sari; Tri Saswandi; Pretty Elisa Ayu Ningsih; Nining Huriati; Rodiyal Ihsan (IICLS (Indonesian Institute for Corporate Learning and Studies), 2023)
This literature review delves into the intricate landscape of teaching the Simple Past Tense to university students, offering a analysis of existing scholarship to unravel challenges, innovative strategies, and future research directions. Recognizing the diverse linguistic backgrounds of students, the review addresses the impact of first language interference and emphasizes the need for tailored instructional approaches. Cultural nuances are explored as pivotal factors influencing tense acquisition, advocating for culturally responsive pedagogy to enhance comprehension and foster a deeper connection between students and grammatical structures. Task-based learning emerges as a promising strategy, supported by studies showcasing its efficacy in providing real-world contexts for applying the Simple Past Tense. Technology integration is examined as a dynamic tool for reinforcing grammatical concepts, with discussions centering on best practices to ensure effective implementation. The implications for educational practice underscore the importance of interactive and engaging approaches, urging educators to leverage task-based learning and technology in language programs. Professional development opportunities are highlighted as essential for enhancing educators' cultural competence and technological proficiency. The review identifies gaps in the literature, suggesting avenues for future research. Specific student populations and longitudinal studies are emphasized, aiming to deepen our understanding of Simple Past Tense acquisition in diverse contexts. The synthesis of findings provides practical insights for educators, researchers, and policymakers, guiding the continual improvement of language education practices and ensuring university students develop the communicative competence essential for academic and professional success.